MICROBIOTIA AND BONE PHYSIOLOGY THE INFLUENCE OF INTESTINAL MICROPHORA ON OSTEOGENESIS - Azizov Dilmurod Homidzoda; Muzaffarov Omon Maratovich (Western European Studies, 2025)
This article analyzes the physiological influence of intestinal microflora on bone tissue metabolism and osteogenesis processes based on theoretical sources. The effect of short-chain fatty acids (SCFA) produced by microflora, the immune system's inflammatory response and mineral metabolism on the activity of bone cells - osteoblasts and osteoclasts is explained. Also, the role of microflora in bone density and remodeling is revealed based on the "microflora-immune-bone axis" model. The fact that this topic has been poorly studied in the Central Asian region emphasizes the need to develop dietary and pharmacological approaches appropriate to local conditions in the future. The article contains scientific conclusions based on in-depth theoretical analysis, rather than on applied research
Keywords: Intestinal microflora; osteogenesis; bone metabolism